Profesionalisme Amil Zakat dalam Meningkatkan Kesejahteraan Umat - Linge, Abdiansyah (YASIN, 2023)
Regulations regarding the management of zakat are quite strong in Indonesia and Aceh Province, from laws to qanuns and governor regulations strengthening zakat in improving people's welfare. If the existing zakat regulation is not managed by amil zakat who understand the management and objectives of ZIS, it will degrade the function of zakat in increasing welfare or creating distribution justice in society. Using the mepiris method, this paper describes the role of amil zakat in collecting and distributing zakat to increase the professionalism of amil. The role of zakat, infak, sadaqoh as economic instruments to distribute justice in society which is understood by amil to be the goal in managing zakat and building synergy between institutions that have the same goals will further enhance the role of ZIS, these goals and synergy are built with professional management that will build trust muzaki and mustahik in the management of zakat.